Reappraisal of the taxonomic status of Amphisbaena prunicolor (Cope 1885) and Amphisbaena albocingulata Boettger 1885 (Amphisbaenia: Amphisbaenidae) - Perez, Renata; Ribeiro, Síria; Borges-Martins, Márcio (Zootaxa, 2012)
We revised the taxonomic status of Amphisbaena prunicolor and A. albocingulata, two taxa traditionally recognized assubspecies of A. prunicolor in the A. darwini complex. Despite some authors elevated both taxa to the specific rank, itstaxonomic decisions were made without specific commentaries and/or proper diagnostic characters. The comparison ofmorphological characters between the two taxa with other similar species, associated with A. darwini (A. darwini, A.heterozonata, A. munoai and A. trachura), revealed a unique combination of diagnostic characters. Amphisbaena pruni-color and A. albocingulata were considered distinct species, diagnosable by the presence of the postmalar row in A. pru-nicolor, absent in A. albocingulata and by the ventral colour pattern uniform (pale brown) in A. albocingulata andcheckerboard (brown-purplish and white) in A. prunicolor. We also provided a redescription of the two species, information on intraspecific variation in A. munoai and suggested the extension of the distribution of A. darwini to southern Brazil.